Implementatioin of Enhanced Transitional Communication Interface Between Mediums Using Adaptive Techniques - Chavakula, N L Sujatha; Pravin, A.; Durga, S. Kanaka; Mallikarjuna, G. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Â Implementation of an innovative and interactive device which is having the capability of changing its own properties with dynamic nature is presented in this project. This project acts as mediator between mediums. Data through water is a challenging task in now a day. Due to random change of properties like water flow, density; framed data energy may changes. So, modulation schemes have to be changed dynamically depends up on flow and density of water. At the receiver side GSM technology is used to re-send the data. Here GSM is used as interface device between water and air.